Modified Magnetic Nanocomposites with 2-Aminobenzothiazole as a Selective Adsorbent for Dispersive Magnetic Micro-solid Phase Extraction of Ultra-trace Amounts of Cadmium in Environmental and Food Samples by Thermospray Flame Furnace Atomic Absorption Spectrometry - de Oliveira, Pâmela Caires; Roveda, Liriana Mara; Ruis, Lucimara Ramires Pereira; dos Santos, Paula Mantovani [UNESP]; Tarley, César Ricardo Teixeira; de Carvalho, Adriana Evaristo; Roman, Daiane; Corazza, Marcela Zanetti (Springer Nature, 2025)
This study reports for the first time the synthesis and analytical performance of two novel magnetic nanocomposites-based silica-coated and carbon nanotubes thiol (2-aminobenzothiazole – ABT) functionalized as adsorbents for preconcentration of cadmium ions in water, cigarette and food samples by dispersive magnetic micro-solid phase extraction (DM-µ-SPE) and determination by thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS). The synthesized materials were characterized by Fourier infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), nitrogen adsorption–desorption, and thermogravimetric analysis (TGA). The pH was investigated univariately while other parameters that influence the DM-µ-SPE were investigated using a two-level (24) full factorial design. As optimized conditions, pH 7.0 and 6.0; 20 mg of nanoparticles; HNO3 1.5 M as eluent and 2 min and 8 min as elution time, were found to m-SiO2-ABT and MMWCNT-ABT, respectively. The method also showed good linearity in the range of 1.0 to 10.0 µg L−1 (r2 ≥ 0.99) and of 2.0 to 20.0 µg L−1 (r2 ≥ 0.99), and low limits of detection (0.02 and 0.11 µg L−1) to m-SiO2-ABT and MMWCNT-ABT, respectively. The nanocomposites, m-SiO2-ABT and MMWCNT-ABT, can be regenerated without significant adsorption capacity loss for ten cycles, yielding recovery percentages of analytical signal of 93.04% and of 103.2%, respectively. The analysis of different water samples (tap water and mineral water), tobacco, green tea, and rice was carried out without matrix interference, yielding recovery values ranging from 88 to 104%.
Keywords: Dispersive microextraction solid phase; Functionalization; Magnetic adsorbents; Metal; Thiol ligands; TS-FF-AAS